Comparative study of fatty liver induced by methionine and choline-deficiency in C57BL/6N mice originating from three different sources - Kim, Sou Hyun; Lim, Yong; Park, Ju Bin; Kwak, Jae-Hwan; Kim, Keuk-Jun; Kim, Joung-Hee; Song, HyunKeun; Cho, Joon Young; Hwang, Dae Youn; Kim, Kil Soo; Jung, Young-Suk (Laboratory animal research, 2017)
Non-alcoholic fatty liver disease (NAFLD) is believed to be the most prevalent liver disease worldwide and a major cause of chronic liver injury. It is characterized by lipid accumulation in the absence of significant alcohol consumption and frequently progresses to steatohepatitis, liver fibrosis, and hepatocellular carcinoma. Although many studies have been conducted to better understand NAFLD since it was first recognized, there are still many gaps in knowledge of etiology, prognosis, prevention and treatment. Methionine-choline deficient (MCD) diet, a well-established experimental model of NAFLD in rodents, rapidly and efficiently produces the clinical pathologies including macrovesicular steatosis and leads to disease progression. In this study, we measured the response to MCD diet in C57BL/6N mice obtained from three different sources; Korea NIFDS, USA, and Japan. We evaluated changes in body weight, food consumption, and relative weights of tissues such as liver, kidney, gonadal white adipose tissue, inguinal white adipose tissue, and brown adipose tissue. These basic parameters of mice with an MCD diet were not significantly different among the sources of mice tested. After 3 weeks on an MCD diet, histopathological analyses showed that the MCD diet induced clear fat vacuoles involving most area of the acinus in the liver of all mice. It was accompanied by increased serum activities of alanine aminotransferase and aspartate aminotransferase, and decreased levels of serum triglyceride and cholesterol. In conclusion, the response of C57BL6N mice originating from different sources to the MCD diet showed no significant differences as measured by physiological, biochemical, and histopathological parameters.